The concept and sense of teacher training in pedagogy: the perspective of the course graduates - Perez, Deivis [UNESP]; Oliveira, Sabrina Orgado (Pontificia Univ Catolica Rio Grande Do Sul, 2015)
This study examined the definition and sense of education for teachers lived in the degree in Pedagogy for teachers. The research problems were: 1) What is the definition of teacher training and the locus in Science Education for voluntary research? 2) What is the meaning given to training in pedagogy? Three teachers participated with typical profile of the educator in the country, according to the 2007 School Census. Use a qualitative research approach and conducting case study. Data were collected through by applying questionnaires and conducting individual and collective interviews. The results show that study participants consider that the locus of teacher education is the pedagogy itself, as a scientific field, and that the term refers to imposing training and indoctrination of teaching professionals action that opposes the ideal of partnership educational process between teachers and their students graduation. There was constant tension between the meanings attributed to the pedagogy course, considered, in some moments, far from the theoretical and practical, and in other situations perceived as facilitating the appropriation relevant to the work of teachers and academics sociopolitical knowledge.
Keywords: Education; Formation of the pedagogues; Sense